Fungsi Hukum dalam Pembangunan Ekonomi - Fachrodin Fachrodin (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2019)
Abstract: This journal entitle the Function Punish In Economics Development, what at one blow become the main problem studied. In the effort giving relevant input upon which basis for conduct the economic law development, it is important to know role punish to economic area. With this step will be able to be known the economic area demand at law area which can be made by a worthwhile input to support the economic growth. This article is inclusive of research punish the convergent normatif at substance punish the primary and sekunder. Problems studied by through legislation approach (statue approach) and approach analyse the concept punish the (analitical conseptual approach). internal issue Formula this study is: 1) How relation of among law economicly 2) How function punish in economic development? Pursuant to inferential bibliography research that: 1) Between law and economic have the such correlation sliver between both. In microeconomic context, what its scope include; cover the business transaction from all economic perpetrator, stand in need of the law order which must have to be obeyed by the parties 2) Function And role punish very strategic in development in economic area. Extant law of regulation function to guide, to giving sanction guidance, and appliance for the merekayasa of social and economic life. Law function as medium to reach the target of economics development.